Experimental investigation on geomechanical properties of tropical organic soils and peat - Kim Huat, Bujang; Asadi, Afshin; Kazemian, Sina (Science Publications, 2009)
Problem statement: Organic soils and peat were believed to be geotechnically problematic due to their very high compressibility, very low shear strength and difficult accessibility. Although conventional soil mechanics theory could be applied to the soils, it was found that important anomalies existed which required special considerations. Correlations between geomechanical parameters for the soils were known to be important for geotechnical engineers to be able to obtain suitable design parameters, as well as to find suitable construction techniques on these soft materials. Approach: To evaluate the geomechanical characteristics of the soils, field and laboratory investigations were carried out according to the organic contents. To achieve such purpose, the soils samples having different organic contents from several locations in Malaysia were collected to determine the correlations of various geomechanical properties of the soils. The classifying tests were determined based on the test procedures according to the British Standard Institution. The compressibility behavior of the soils was determined by Rowe cell consolidation test. Results: The test results indicated that the natural water contents, organic contents, liquid limits, specific gravities and bulk densities ranged from 150-700%, 50-95%, 180-500%, 1.05-1.9 and 0.8-1.2 Mgm-3, respectively. The compression indexes of the soils were higher than Hobbs and Skempton’s approximations. Conclusion/Recommendations: The soils properties were highly dependent on the organic contents. With an increase in organic content, the natural water content, liquid limit, compression index and void ratio increased and the specific gravity and bulk density decreased. Furthermore, the hemic and sapric peat had lower shear strength than the fibrous peat. The first-of-its-kind study was the first step on the road to persuade researchers to improve these problematic soils.